Orthotopic kidney transplantation is a possible solution in difficult situations - D. V. Perlin; A. V. Terentyev; T. S. Vasiliev; Ya. N. Dankov (Трансплантология (Москва))
Background. Kidney transplantation is the most preferable definitive treatment for the end-stage renal disease. Often, patients who need an organ transplantation have peculiar anatomical features that require a non-standard approach to performing this surgery.Objective. To present a clinical case of orthotopic kidney transplantation in a patient with occlusive thrombosis of the external iliac veins.Material and methods. A 31-year-old patient with stage 5 chronic kidney disease and occlusive thrombosis of the external iliac veins being prepared for a related donor kidney transplantation.Results. Orthotopic kidney transplantation was performed. In order to ensure a sufficient length of the donor kidney artery and the convenience of its anastomosis, a segment of the recipient's splenic artery was used. The venous and ureteral segments of the graft were anastomosed end-to-end with the recipient's renal vein and ureter, respectively. After the surgery completion, the graft function was immediate. In the postoperative period, three-component immunosuppressive therapy was used. At the time of discharge, plasma creatinine was 0.15 mmol/L.Conclusion. Orthotopic kidney transplantation should be considered as an alternative solution in case of obliteration, thrombosis or atherosclerotic lesion of the recipient's iliac vessels. The method can be used in recipients with two or more previous transplants.